(untitled) (Nepal Journal of Neuroscience, 2023)
Introduction: Meningioma is the most common benign primary intracranial tumour after glioma. Meningioma occuring in intraventricular region is very rare. When located in intraventricular space, majority of intravemtricular meningioma (IVM) are located in lateral ventricles. Material and methods: This is a Study of four cases of intraventricular meningioma in Madras medical College from January 2022 to December 2022. In this study, the symptoms, MRI findings, operative procedure, histology images, surgical outcomes and a detailed review is done from various literature. Results: Among the various symptoms, headache, disturbance in vision, changes in cognition and speech disturbance were commonly found. The site of all the lesion was in the lateral ventricle. MRI was used to confirm the diagnosis before surgery. In our patients, the intraventricular meningioma was completely excised via parietal craniotomy or temporoparietal craniotomy based on the location of the tumour. The tumour was completely excised in all four patients. Histologically it was meningothelial meningioma in all 4 patients. Conclusion: From our case series we observed that all the IVM were WHO grade I and total excision is possible in intraventricular meningiomas with properly planned surgical trajectory with minimum post operative morbidity.